Genesis of the Heroin-Induced Addictive Process: Articulation Between Psychodynamic and Neurobiological Theories - Scarna, Hélène (Frontiers in Psychiatry, 2020)
Psychotherapeutic consultations of drug addict’s patients in a Care, Support and Prevention Center in Addictology led us to propose several hypotheses on the genesis of addiction and its articulation with currently available neurobiological data. This care center dispenses both pharmacological maintenance medications for heroin dependence, such as methadone or buprenorphine, and psychological support. Our first hypothesis posits that the addictive process is driven by the narcissistic vulnerability of these patients, its neurobiological foundations being mainly mediated by the activation of endogenous opioid systems. Drug use/abuse could be a way to make arise the “True Self”, therefore overcoming the defensive system’s set up to protect oneself from early traumas. The neurobiological impact of traumas is also developed and articulated with psychodynamic concepts, particularly those of Winnicott. Additionally, functions of addiction such as defensive, anti-depressant roles and emotional regulation are discussed in relationship with their currently known neuroscientific bases. Although the experience in the psychodynamic clinic is at a level of complexity much higher than what is currently accessible to the neurosciences, most of the research in this domain stays in line with our psychological understanding of the addictive process. Finally, we outline some critically sensitive points regarding the therapeutic support.